Formation of citizens rights to a healthy environment in Kazakhstan (Journal of actual problems of jurisprudence, 2019)
The article examines the processes of development of the right of citizens to a healthy environment inKazakhstan. A few decades ago, the right to a safe and supportive environment was not aware of legal science.Appeared in the twentieth century, it was quick in its development, because of the global environmentalproblems that contributed to the strengthening of its status, which allowed the transfer to basic rights suchas the right to life. The study shows the development of the regulatory framework of the Kazakh SSR,Soviet Union and for the protection of the environment and environmental policy inefficiency of the Sovietperiod, due to the extensive activities of the USSR, which inflicted irreparable damage to the environmentin Kazakhstan.Keywords: right to a healthy environment, history of development of the right of Kazakhstan, internationalacts.